Tecnologia, fetiche e ideologia: um estudo sobre Non Fungible Tokens - Maia, Eduardo Santos (2024)
The novelty of the subject and the small amount of publicity outside specialized circles turn non-fungible tokens (NFTs) something that is still mysterious and lacks materiality. In response to the question: "What are NFTs?", we will characterize them as digitally created assets that can represent virtual or non-virtual objects, which are registered on a blockchain, traded using cryptocurrencies and protected using cryptography. The research is linked to a class perspective, as an intellectual effort to confront and defend the overcoming of the capitalist order, inserting itself into the gaps in content and approach on the subject. The aim is to make a contribution to the existing knowledge that also take on the perspective of the working class in order to think about a diferente sociability from the current one. It is, therefore, necessary to analyze NFTs within capitalist sociability, as an object that arose in a specific context, under specific conditions and with underlying political-ideological values. The effort to understand specific contemporary phenomena can reveal clues that help us understand the capitalist system as a whole. In other words, NFTs offer an opportune way of shedding light on contemporary capitalism through the articulation between recent technological development and the theoretical tradition begun by Marx. The purpose of this thesis is to investigate the links between new technologies, fetishism, alienation, and capitalist ideology, based on the phenomenon of NFTs. In this process, critical reflections on the categories of fetishism, alienation and ideology will be developed in order to understand the process by which NFTs, as an example of new technology, correspond to a fetish and thus contribute to the reproduction of capitalist ideology. As a working hypothesis, we sought to verify whether, and if so, how technologies that present themselves as revolutionary within the capitalist framework conform to capitalist society by exacerbating dominant social relations and contributing to the reproduction of its ideology, based on the case of NFTs. To this end, a bibliographical research was carried out, fulfilling the objectives of substantiating the object and positioning the research critically against current views. The scheme of successive readings, from exploratory to interpretative readings, met the need to discuss the subject critically and interpret it from our position and purpose. The theoretical framework was based on the Marxist tradition, taking up classic categories and authors and articulating them with contemporary authors. Through this process, the ways in which NFTs contribute to the reproduction of capitalist society were identified. Their discursive role and their role in propagating capitalist values go alongside the functions of enabling channels for capital appreciation and as a means of commodifying previously non-marketable objects. NFTs are both a reflection of the capitalist mode and an element that reinforces its logic, constituting fetishes.